2017
DOI: 10.1007/s00213-017-4768-5
|View full text |Cite
|
Sign up to set email alerts
|

Odor cueing during slow-wave sleep benefits memory independently of low cholinergic tone

Abstract: RationaleSleep-dependent memory consolidation depends on the concerted reactivation of memories in the hippocampo-neocortical system. The communication of reactivated information from the hippocampus to the neocortex is assumed to be enabled by low levels of acetylcholine, particularly during slow-wave sleep (SWS). Recent studies suggest that the reactivation of memories does not only occur spontaneously but can also be externally triggered by re-presenting learning-associated cues during sleep.ObjectivesHere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Note that mathematical models of memory posit competition between items linked to a context 40 ; however, these models have focused on data from wake, not sleep, and it is possible that memory systems operate differently during sleep. For example, low levels of acetylcholine during slow-wave sleep may put the hippocampus into a strong retrieval mode that makes it possible to retrieve more traces at once 41,42 (but see 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Note that mathematical models of memory posit competition between items linked to a context 40 ; however, these models have focused on data from wake, not sleep, and it is possible that memory systems operate differently during sleep. For example, low levels of acetylcholine during slow-wave sleep may put the hippocampus into a strong retrieval mode that makes it possible to retrieve more traces at once 41,42 (but see 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Slow oscillations and spindles were detected during NREM epochs (i.e., stage 2, and SWS) using established algorithms (spindles: Klinzing et al 2016Klinzing et al , 2018Mölle et al 2011;slow oscillations: Mölle et al 2002;Ngo et al 2013). The algorithms are described in detail in Muehlroth et al (in press).…”
Section: Spindle and Slow Oscillation Detectionmentioning
confidence: 99%
“…Specifically, authors observed an increase in EEG power in the frontal delta (1.5–4.5 Hz) and parietal fast spindles (13–15 Hz), two EEG activities purported to coordinate the reactivation and consolidation of declarative memories from the hippocampus to the cortical networks . Interestingly, it has been recently suggested that the beneficial effect of olfactory‐induced TMR seems not to rely on the same neurophysiological mechanism underlying neural reactivation during sleep . Indeed, a recent pharmacological study observed a benefit of odor stimulation during SWS even when the cholinergic tone of the participants was increased using physostigmine, an acetylcholinesterase inhibitor that effectively increases the accumulation of acetylcholine at the synaptic level .…”
Section: Tmr and Declarative Memorymentioning
confidence: 99%
“…Interestingly, it has been recently suggested that the beneficial effect of olfactory‐induced TMR seems not to rely on the same neurophysiological mechanism underlying neural reactivation during sleep . Indeed, a recent pharmacological study observed a benefit of odor stimulation during SWS even when the cholinergic tone of the participants was increased using physostigmine, an acetylcholinesterase inhibitor that effectively increases the accumulation of acetylcholine at the synaptic level . These results were surprising, since the authors expected that physostigmine would block hippocampal–neocortical communication (i.e., systems consolidation).…”
Section: Tmr and Declarative Memorymentioning
confidence: 99%